Clinical study and management of small bowel obstruction in 20 cases in a large tertiary care teaching public health hospital in Department of General Surgery - Mehta, Sudhir G.; Bajpai, Achint; Kumar, Saravana (International Surgery Journal, 2019)
Background: Small bowel obstruction is one of common and most challenging emergency faced by one in surgical practice. Bowel obstructions account for approximately 20% of all surgical admissions in patients with acute abdominal conditions. The aim of the study was to evaluate age and sex distribution along with different etiological factors in age groups, clinical features among with different etiological factors, benefits of early surgical intervention, causes of mortality and morbidity. Methods: A retrospective observational study was conducted in 20 patients for period of two years. All cases above age of 18years are included. Patients who are pregnant, with history of confirmed and strongly suspected peritoneal carcinosis, undergoing radiotherapy of the abdominal region are excluded from the study. Results: 20 cases with 60% males and 40% females were included in the study and majority of patients were between age group of 41 to 60 years (55%). Pain abdomen was the most common symptom. Abdominal tenderness was the most common sign present in all patients. Mortality rate was 20% out of which 40% death rate was present in patient operated after 24 hours of admission. Septicaemia was the most common cause of death. Conclusions: So the intra-abdominal adhesions are the commonest cause of small bowel obstruction while strangulation or obstructed hernia may account for high mortality. Conclusively it can be said that early detection and complete treatment including timely surgery are the essential aspects to decrease morbidities and ultimately decrease mortality.